2020
DOI: 10.1177/1533033820971306
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SPP1 Suppresses Progression of Tongue Cancer by Mediating the PI3K/Akt Signaling Pathway

Abstract: Background: In the present study, we aimed to find an effective target for the treatment of tongue cancer using gene chip screening and signal pathway research. Methods: We used microarray screening and gene expression profile analyses to find important differentially expressed genes in tongue cancer. We constructed a protein-protein interaction network, and used enrichment analysis of the Kyoto Encyclopedia of Genes and Genomes to screen for important genes. We then silenced the genes of interest in SCC154 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…6 (See legend on previous page.) signaling pathway in tongue cancer [33]. Besides, high expression of SPP1 is correlated with poor survival in several cancers [34,35].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6 (See legend on previous page.) signaling pathway in tongue cancer [33]. Besides, high expression of SPP1 is correlated with poor survival in several cancers [34,35].…”
Section: Discussionmentioning
confidence: 97%
“…SPP1-CD44 axis could promote cancer stemness in pancreatic cancer [ 32 ]. It was reported that lacking of SPP1 inhibits progression by mediating the PI3K/Akt signaling pathway in tongue cancer [ 33 ]. Besides, high expression of SPP1 is correlated with poor survival in several cancers [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research found inhibition of the SPP1 gene may have therapeutic benefits for tongue cancer and may be a useful target for therapy (Zhang et al, 2020). Moreover, in pancreatic tumor microenvironment factors, the SPP1-CD44 axis can promote cancer stemness (Nallasamy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancer (CRC), SPP1 was highly upregulated and increased CRC metastasis by promoting epithelial-mesenchymal transition (EMT) ( Xu et al, 2017 ). In addition, previous research found inhibition of the SPP1 gene may have therapeutic benefits for tongue cancer and may be a useful target for therapy ( Zhang et al, 2020 ). Moreover, in pancreatic tumor microenvironment factors, the SPP1-CD44 axis can promote cancer stemness ( Nallasamy et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to find more accurate biomarkers to detect at an early stage and monitor disease progression. According to the previous studies, SPP1 is overexpressed in various cancer types ( Xu et al (2017) ; Choe et al (2018) ; Zhang et al (2020) ) and identified as a prognostic factor ( Li et al (2018) ; Chen J et al (2019) ; Guo et al (2020) ), while to our knowledge, no study has explored the relationship of SPP1 expression and cervical cancer. In our study, we attempted to explore the potential mechanism of SPP1 in promoting cervical cancer and its feasibility as a molecular biomarker.…”
Section: Discussionmentioning
confidence: 99%